ANALISIS MISSING FACTOR’S YANG PERLU DIINJEKSIKAN PADA KEMITRAAN USAHA ANTARA PETANI DENGAN PT. TTDS MITRA GARUDA DALAM MENANAM KACANG TANAH BENIH UNGGUL DI KAWASAN MERU BETIRI KABUPATEN JEMBER - S, Urip (Jurnal Sosial Ekonomi Pertanian, 2009)
This research yields conclution and recommendation; conclution yielded inter alia : 1. In initial years blazed the way actually PT. TTDs has obtained respond either from farmer publick Meru Betiri, farmer shows its (the readiness) to plant a bit of blood peanut, 2 constraint having the character of external namely alteration grade specified by parent corporation to cause hit of PT. TTDs Mitra Garuda and cultivator farmer. And this condition have time to stop whereas business activity is extending areal peanut  corp in Meru Betiri. As for recommendation given inter alia : increases professionalism of resoursess good man area to be internal of business and farmer through process learning by doing, builds internal of net working which is better to obtain access to increase position bargains so that company can involve influences policy decisions taken by holding companies when the decisions touchs importance of wide public especially farmer pembudidaya a bit of blood peanut. Key word : Competitive advantage, Comparative advatage, Batu Apple